SOUTH AFRICA’S QUIXOTIC HERO AND HIS NOBLE QUEST – CONSTITUTIONAL COURT JUSTICE ALBIE SACHS AND THE DREAM OF A RAINBOW NATION - Stephen Peté (Obiter, 2021)
Albie Sachs has always been clear-sighted in his vision of a rainbow nation at the southern tip of Africa, characterised by tolerance and mutual respect among and between its citizens. Using the well-known story of Don Quixote de la Mancha as a metaphor, this article sets out to chart the “quest” undertaken by Albie Sachs in pursuit of his noble dream. It traces a number of important personal and political transitions that he has made along the way, from his initial emphasis on solidarity and revolutionary struggle, to his later focus on issues of diversity and tolerance. The article touches briefly on aspects of Albie Sachs’s inspiring dignity jurisprudence which it applauds, but then poses the question as to whether or not his views represent real hope to a country which, a decade and a half after the end of apartheid, remains fractured and traumatized.